2015
DOI: 10.1002/jmv.24284
|View full text |Cite
|
Sign up to set email alerts
|

Episodic detection of human papillomavirus within a longitudinal cohort of young women

Abstract: Redetection of a type-specific human papillomavirus (HPV) infection may represent reinfection. However, a growing body of literature suggests that reactivation of HPV is common and that episodic detection of a HPV infection may represent reactivation of a persistent virus. A cohort of prospectively followed adolescent women (N = 150), ages 14-17, was observed on average 6.4 years. The authors describe the redetection of 37 HPV types and associated factors of redetection of high-risk (HR) and low-risk (LR) type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Consistent with findings for the viral RNA reads, we found dysregulated expression of fewer 377 genes in IV infection-induced tumors than in local infection-induced tumors. Although these two 378 different infection routes induced different numbers of genes with altered expression, we found 379 that the majority of the genes with significantly different expression were common to all tumors infections are thought to clear spontaneously but the process often occurs over a lengthy time 388 period of 1-2 years or more (Shew et al, 2015). In 10-20% of that HPV infected population, 389 infection with the same viral species reappears at a later date (Martinez and Troconis, 2014).…”
Section: Viral Dna Was Detected In Blood Samples Of Crpv Infected Rabmentioning
confidence: 82%
“…Consistent with findings for the viral RNA reads, we found dysregulated expression of fewer 377 genes in IV infection-induced tumors than in local infection-induced tumors. Although these two 378 different infection routes induced different numbers of genes with altered expression, we found 379 that the majority of the genes with significantly different expression were common to all tumors infections are thought to clear spontaneously but the process often occurs over a lengthy time 388 period of 1-2 years or more (Shew et al, 2015). In 10-20% of that HPV infected population, 389 infection with the same viral species reappears at a later date (Martinez and Troconis, 2014).…”
Section: Viral Dna Was Detected In Blood Samples Of Crpv Infected Rabmentioning
confidence: 82%
“…The present study found an association between previous STI and the risk of infection by HR-HPV types. It should be stressed that the adolescent population exposed to risky sexual behaviour should be screened for these infections which could participate in HPV persistence, redetection and tumour carcinogenesis through cumulative effects [36]. …”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the elevated cancer risk associated with particular HPV types results from a small fraction of persistent infections (18). Longitudinal studies, however, have shown that hosts can be infected repeatedly (19). Although type-specific antibodies may provide modest protection against future infection in women (20), serum antibody is not a marker of immune protection in men (21,22).…”
Section: Significancementioning
confidence: 99%